2018
DOI: 10.1111/apt.14817
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: Tong‐Xie‐Yao‐Fang granules versus placebo for patients with diarrhoea‐predominant irritable bowel syndrome

Abstract: During a 4 week trial, TXFY granules were superior to placebo in controlling symptoms of IBS-D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 28 publications
0
68
0
Order By: Relevance
“…TXYF also yielded improvements in several secondary outcomes including abdominal pain, bloating, stool frequency and consistency. Interestingly, TXYF treatment benefits persisted several weeks beyond the active treatment period . A calculated number‐needed‐to‐treat (NNT) of 5 for adequate relief using TXYF compared favourably to contemporary medications approved for IBS‐D, such as eluxadoline (NNT = 12.5) and rifaximin (NNT = 10.4) .…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…TXYF also yielded improvements in several secondary outcomes including abdominal pain, bloating, stool frequency and consistency. Interestingly, TXYF treatment benefits persisted several weeks beyond the active treatment period . A calculated number‐needed‐to‐treat (NNT) of 5 for adequate relief using TXYF compared favourably to contemporary medications approved for IBS‐D, such as eluxadoline (NNT = 12.5) and rifaximin (NNT = 10.4) .…”
mentioning
confidence: 65%
“…In a recent issue of AP&T , Chen and colleagues convincingly demonstrated Tong‐Xie‐Yao‐Fang (TXYF) to be effective in reducing the global symptoms of diarrhoea‐predominant irritable bowel syndrome (IBS‐D) . Perhaps unfamiliar to the allopathic physician, the traditional Chinese Medicine (TCM) herbal preparation TXYF has been used for hundreds of years as a remedy, not for IBS, but rather “liver stagnation and spleen deficiency”.…”
mentioning
confidence: 99%
“…Chen et al, conducted a double-blind placebo-controlled randomized trial to study the efficacy of TXYF for treating IBS-D. The study concluded that use of TXFY was superior to placebo in controlling symptoms of IBS-D with low adverse event rate [20].…”
Section: Bodymentioning
confidence: 99%
“…Rhizoma Atractylodis Macrocephalae and Citri Reticulatae Pericarpium strengthen spleen to eliminate dampness while Paeoniae Radix Alba and Saposhnikoviae Radix soothe liver to regulate qi. These four herbs contained in TXYF by orchestrating the function of spleen and liver to relieve symptoms of IBS-D. A recent study has proved that TXYF is e cacious in the relief of abdominal pain and bloating in IBS-D patients with only sporadic adverse events (9). But there is a scrap of contradictory evidence that TXYF has little impact on the amelioration of symptoms of IBS-D (10).…”
Section: Introductionmentioning
confidence: 99%